The volatility and future of democracy in Asia - Yang, Alan Hao; Xiao, Xinhuang (London : Routledge, 2021)
This book explores the volatile and uncertain future of democracies in Asia through typological analysis of the diverse patterns of Asian countries. Detailed analysis and extensive case studies featured throughout this edited volume unveil democracies in the process of being consolidated, such as Taiwan and South Korea; precarious democracies, such as Indonesia, Malaysia, and the Philippines; states that are experiencing setbacks and a retreat from democracy, such as Thailand and Myanmar; and finally, states that are still resisting democracy, including China. Key findings articulate that Asian democracies do not follow existing models or patterns--such as that of Western democracy--but are instead lively, emergent works in progress. Environments in which democracy is practiced in Asia reflect local people's pluralistic imagination of democracy; hence a comparative thematic approach is adopted. Contributors originate from Japan, Korea, Malaysia, the Philippines, Taiwan, and Thailand, each presenting regional insights into the unique challenges and movements of their respective nations, from staging protests in Bangkok to military coup in Myanmar. Opening new dialogue in the study of democracy, The Volatility and Future of Democracies in Asia will appeal to students and scholars of political science, comparative politics, international development, democracy studies, and Asian studies more broadly. .
Keywords: Democracy -- Asia; Democratization -- Asia; Political stability -- Asia; Asia -- Politics and government -- 21st century; POLITICAL SCIENCE / Political Ideologies / Democracy; POLITICAL SCIENCE / General